Diversification of Seaweed and Milkfish Processing in Improving the Economy of Coastal Community Families - Najib, Marhawati; Astuty, Sri; Hidayat, Wahyu; Irwandi, Irwandi; Subur, Hikmayani; Nur’aeni, Nur’aeni (Universitas Lambung Mangkurat, 2025)
The purpose of this community service is to empower housewives by providing training on how to process seaweed, which is rich in nutrients and a source of protein, into products with high economic value. Through socialization, instruction, hands-on practice, and mentorship, content is provided through the Participatory Learning and Action (PLA) approach. The findings are that most housewives are unemployed and have a lot of free time not used for productive activities due to the lack of knowledge and skills in processing seaweed. The results of implementing this community service are an increase in knowledge and skills by 98% in processing seaweed combined with milkfish into products with economic value in the form of mini pastels, meatballs, and nuggets. Product marketing training activities: by practicing using online media, only eight people (20%) can understand how to use social media well. The rest of the participants do not have an Android cellphone, and some have cellphones but do not understand how to use social media. In addition, there are also obstacles to understanding technology, especially among older people or those less familiar with digital devices. This seaweed processing and marketing activity is expected to provide added value to seaweed commodities and provide additional income for seaweed farming families.